Reactive Oxygen Species Link Gene Regulatory Networks During Arabidopsis Root Development - Mase, Kosuke; Tsukagoshi, Hironaka (Frontiers in Plant Science, 2021)
Plant development under altered nutritional status and environmental conditions and during attack from invaders is highly regulated by plant hormones at the molecular level by various signaling pathways. Previously, reactive oxygen species (ROS) were believed to be harmful as they cause oxidative damage to cells; however, in the last decade, the essential role of ROS as signaling molecules regulating plant growth has been revealed. Plant roots accumulate relatively high levels of ROS, and thus, maintaining ROS homeostasis, which has been shown to regulate the balance between cell proliferation and differentiation at the root tip, is important for proper root growth. However, when the balance is disturbed, plants are unable to respond to the changes in the surrounding conditions and cannot grow and survive. Moreover, ROS control cell expansion and cell differentiation processes such as root hair formation and lateral root development. In these processes, the transcription factor-mediated gene expression network is important downstream of ROS. Although ROS can independently regulate root growth to some extent, complex crosstalk occurs between ROS and other signaling molecules. Hormone signals are known to regulate root growth, and ROS are thought to merge with these signals. In fact, the crosstalk between ROS and these hormones has been elucidated, and the central transcription factors that act as a hub between these signals have been identified. In addition, ROS are known to act as important signaling factors in plant immune responses; however, how they also regulate plant growth is not clear. Recent studies have strongly indicated that ROS link these two events. In this review, we describe and discuss the role of ROS signaling in root development, with a particular focus on transcriptional regulation. We also summarize the crosstalk with other signals and discuss the importance of ROS as signaling molecules for plant root development.